Life Cycle Assessment of 5-Hydroxymethylfurfural: Feedstock comparison and hotspot analysis - Shyma Suresh,Ahalditha; Darade,Dhanashree Annasaheb (2025)
5-Hydroxymethylfurfural (HMF) is a versatile bio-based platform chemical that can substitute fossil-derived intermediates in polymers, solvents, and fuels, thereby contributing to a fossil-free chemical industry. While first-generation feedstocks such as high-fructose corn syrup have been widely studied, their use raises concerns about competition with food supply. In contrast, second-generation residues such as sugar beet pulp (SBP) represent a more sustainable alternative, though their environmental performance has been insufficiently quantified. This study performs a cradle-to-gate life cycle assessment (LCA) of HMF production from SBP under Swedish conditions, using 1 kg of HMF as the functional unit. Foreground inventories were compiled from recent literature and pilot-scale studies, while background processes were modeled using the Ecoinvent database. The analysis evaluates four midpoint impact categories: climate change, particulate matter formation, freshwater eutrophication, and marine eutrophication and assesses the influence of different regional electricity mixes (Sweden, Norway, Poland, EU and Global). In addition, a location study was conducted to identify potential biorefinery siting options in Skåne based on feedstock availability, infrastructure, and energy integration. The LCA results show that climate change impacts are dominated by dimethyl carbonate production (47%), followed by sugar beet cultivation (31–32%). Particulate matter formation is mainly driven by activated carbon production (>22%) and fossil-based electricity inputs. Freshwater eutrophication arises largely from wastewater ( 41%) and municipal solid waste treatment ( 26%), while marine eutrophication is overwhelmingly linked to sugar beet production ( 86–87%). These findings highlight stage-specific hotspots and the need for targeted mitigation across agriculture, chemical synthesis, energy use, and waste management. The sensitivity analyses further demonstrate that electricity mix strongly shapes the results, with Sweden’s renewable-rich grid lowering impacts compared to fossil-heavy systems such as Poland. Location choices within Skåne also influence outcomes by affecting transport distances and access to renewable energy. Taken together, the findings indicate that while HMF from SBP can offer a sustainable alternative to fossilbased chemicals, its overall performance depends heavily on cleaner energy integration, improved purification methods, and regionally optimized biorefinery siting.
Keywords: Life cycle assessment; 5-Hydroxymethylfurfural (HMF); biomass feedstocks; climate impact; solvent recovery; Swedish energy mix; Skåne siting; biorefinery integration.